2015
DOI: 10.1103/physrevb.91.245135
|View full text |Cite
|
Sign up to set email alerts
|

Role of real-space micromotion for bosonic and fermionic Floquet fractional Chern insulators

Abstract: Fractional Chern insulators are the proposed phases of matter mimicking the physics of fractional quantum Hall states on a lattice without an overall magnetic field. The notion of Floquet fractional Chern insulators refers to the potential possibilities to generate the underlying topological bandstructure by means of Floquet engineering. In these schemes, a highly controllable and strongly interacting system is periodically driven by an external force at a frequency such that double tunneling events during one… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 82 publications
0
61
2
Order By: Relevance
“…Moreover, in Refs. [185,186] it was shown that Floquet Chern insulators with sufficiently strong nearest-neighbour interactions exhibit the phenomenon fractionalisation at fractional fillings. Cold atom experiments managed to realize a fermionic system with topological bands in the laboratory [49].…”
Section: 2mentioning
confidence: 99%
“…Moreover, in Refs. [185,186] it was shown that Floquet Chern insulators with sufficiently strong nearest-neighbour interactions exhibit the phenomenon fractionalisation at fractional fillings. Cold atom experiments managed to realize a fermionic system with topological bands in the laboratory [49].…”
Section: 2mentioning
confidence: 99%
“…Similar schemes can be envisaged to produce synthetic spin-orbit couplings, uniform magnetic fields and topological insulating states with shaken optical lattices [100]. Recently, and in direct analogy with solid-state-physics Floquet topological states [104,105,107,109,375], it has been suggested that (circularly) shaken hexagonal optical lattices could reproduce the physics of graphene subjected to circularly polarized light [see Sect. 2.2 and Refs.…”
Section: Other Relevant Schemesmentioning
confidence: 99%
“…In addition to this aspect, we now have to measure observables that are affected by micromotion describing the dynamics of the Floquet system within a driving period. Whilst this micromotion tends to become negligible for infinite driving frequencies, it alters the states significantly for near-resonant and low-frequency modulation [1,2,4,[28][29][30][31].In this work, we address the previously mentioned challenges in a tractable way by realizing a periodically driven array of double wells [32] occupied by pairs of interacting atoms [33][34][35][36], which allows for a full control of the Floquet state population [27]. The symmetric double well consists of two sites containing two opposite spins, and can be described by a Hubbard model with a tunneling amplitude t, and an on-site interaction U .…”
mentioning
confidence: 99%
“…In addition to this aspect, we now have to measure observables that are affected by micromotion describing the dynamics of the Floquet system within a driving period. Whilst this micromotion tends to become negligible for infinite driving frequencies, it alters the states significantly for near-resonant and low-frequency modulation [1,2,4,[28][29][30][31].…”
mentioning
confidence: 99%